The sustainability of the asian wooden furniture industry - Ratnasingam, J.; Ioras, F. (Springer Science and Business Media LLC, 2003)
This paper attempts to analyze the sustainability of the Asian wooden furniture industry. Despite booming exports, the furniture industry is besieged with stagnating productivity. The growth attributed to rising exports of low-value, contract furniture is not sustainable in the long-term as other cheaper manufacturers emerge. Industry liberalization coupled with the use of skilled workers, and not industrial policy, are the strategic elements for sustainability.